Selection of optimization criteria and factors affecting the cleaning process of repair objects - Dashyvets, Halyna; Дашивець, Галина Іванівна; Garbut, D. (Запоріжжя: ТДАТУ, 2025)
Cleaning technology is one of the key factors determining the technical level of repair and maintenance production. Removal of contaminants is a prerequisite for high-quality servicing of machinery, productive disassembly without damaging dismantled parts, accurate defect detection and inspection, as well as obtaining reliable coatings during galvanic, polymer, surfacing, and other restoration operations. Inefficient cleaning technologies and equipment also negatively affect sanitary and hygienic working conditions and worker productivity. In particular, the quality of component cleaning directly influences the service life of repaired machines.
Keywords: technology; repair objects